Indian constitution's seanless web - Austin, Granville (New Delhi, 1994)
The Indian Constitution is the foundational charter of the Indian Republic. It reflects the preferred values of the Nation and shapes our collective vision of the future. It is not the offspring of a single brain but "the work of many heads and many hands". Under the pressure of debate in the Constituent Assembly, many scattered strands of thoughts used disconnectedly for years but never before comprehended as a whole were picked up, brought together, and woven into a new political fabric whose beauty and symmetry is gradually becoming evident. For the last forty four years the Constitution has provided governing rules for all the cardinal relationships in the land: between the government and the citizens, between the Centre and the States, between the three branches of government, between the various social groups and communities, and between individual citizens themselves.
Keywords: Constitution-India